Changing Trade Patterns after Conflict Resolution in the South Caucasus - Polyakov, Evgeny (World Bank, Washington, DC, 2014)
Since the breakup of the USSR, the South Caucasus region has experienced a range of political conflicts, resulting in a number of hot and cold wars and border closures. The author analyzes the probably short-term impacts of peace in the region as a result of a resolution of the conflict between Armenia and Azerbaijan over the Nagorney Karabakh region and an end to the associated trade blockades, with an emphasis on Armenia, Azerbaijan, and Georgia. The conflict has seriously distorted trade flows in the region, disrupted transport routes, and stifled export and import opportunities for Armenia and Azerbaijan. Georgia has enjoyed higher-than-normal transit through its territory. Trade has stopped in gas (from Azerbaijan to Armenia) and electricity (from Armenia to Turkey). Transport tariffs are unusually high, aggravated by government-imposed transit fees (taxes). Over time, trade restrictions have eased and trading partners have found ways to conduct trade despite closed borders and blockades--but at a cost. Applying a gravity model to regional trade, the author concludes that South Caucasus countries trade enough with the CIS countries and politically friendly neighbors, but too little with the European Union, the United States, and hostile neighbors. Lifting the blockades would alleviate trade distortions and bring about short-term improvements, including: 1) More rational trade flows; 2) A resumption of (or an increase in) regional trade in major commodities such as energy; and 3) Lower prices or higher profit margins (or both) on some important consumption and production goods. With peace, Armenia could more than double its exports if Azerbaijani and Turkish markets open, which could reduce Armenia's trade deficit by a third to a half and increase its GDP by 30 percent. Improving transport routes would produce immediate savings and relieve pressure on domestic prices, especially for energy. Azerbaijan could increase its exports by $100 million, or 11 percent of 1999 levels, reducing its trade deficit by a quarter and raising its GDP by 5 percent. Its exports and imports would benefit from transport savings. Transit through Georgia might decline, but probably not by more than a quarter of the freight service surplus.